Duration of Catarina Virus Infection in the Southern Plains Woodrat (Neotoma micropus) - Milazzo, Mary L. (Mary Ann Liebert, Inc., 2012)
Four adult male, 6 sub-adult, and 7 newborn southern plains woodrats (Neotoma micropus) each were inoculated subcutaneously with 3.1 log(10) median cell culture infectious doses (CCID(50)) of Catarina virus strain AV A0400135 (virus family Arenaviridae). The inoculated animals and the mothers of the newborn animals all became infected and remained asymptomatic. The infections in the adult male woodrats and in the mother woodrats were transient, the infections in 2 (33.3%) of the sub-adult woodrats persisted through month 4 post-inoculation, and 6 (85.7%) of the newborn woodrats were viruric through month 5 post-inoculation. Collectively these findings indicate that the duration of infection in the southern plains woodrat is dependent upon age at exposure to Catarina virus. The results of this study also indicate that chronically infected woodrats persistently shed Catarina virus into the environment.